Legal Review of Positive Fictive Inconsistency in Government Regulations on the Implementation of Risk-Based Business Licencing - Dewa Rizky Pangestu; Sulaksono (NOVUM : JURNAL HUKUM, 2025)
This study examines the OSS-RBA licensing process, which adapts the positive fictitious principle from the Government Administration Law (UUAP) for KTUN implementation. PP 5/2021 underlies the OSS system, adopting this principle. The study addresses issues with OSS licensing applications due to inconsistencies with positive fictitious regulations. Using a normative juridical method with statute, historical, case, and conceptual approaches, it relies on legislation and secondary materials such as books and journals. Indonesia's policies now use technology, including OSS-RBA in PP 5/2021, replacing PP 24/2018. Despite the positive fictitious concept in PP 24/2018 and UUAP, PP 5/2021's implementation is inconsistent, causing licensing delays and legal uncertainty, hindering investment. Improving OSS-RBA is crucial to effectively apply the AUPB principle, creating a transparent, efficient bureaucracy and increasing legal certainty for businesses. This supports sustainable economic growth and enhances Indonesia's global competitiveness. Inconsistencies between licensing practices and regulations like PP 5/2021, and the absence of a Presidential Regulation on legally granted KTUN forms, cause legal uncertainty. Legal remedies include legal construction, ombudsman, residual theory, and establishing a special institution for positive fictitious cases.